The Spec# Programming System: Challenges and Directions - Barnett, Mike; DeLIne, Robert; Fähndrich, Manuel; Jacobs, Bart; Leino, Rustan; Schulte, Wolfram; Venter, Herman (VSTTE 2005: Verified Software: Theories, Tools, Experiments, 2005)
The Spec# programming system [2] is a new attempt to increase the quality of general purpose, industrial software. Using old wisdom, we propose the use of specifications to make programmer assumptions explicit. Using modern technology, we propose the use of tools to enforce the specifications. To increase its chances of having impact, we want to design the system so that it can be widely adopted.